Regional development policy in Galicia: the crossroads of territorial development - Díaz Fernández, José Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The regional development policy is one of the main tools available to the Public Administration to promote a decentralized regional economic development model due to the endogenous potentialities of the different regions. Therefore, the concretion of an indicative policy model destined to be implemented in the Spanish regional territories, as is the case of Galicia, intends to act as a driving force to encourage the economic development of the territory based on its internal potentialities. Galicia, for a long time in its history, has been suffering from territorial interlocking.